High Sensitivity C-Reactive Protein an inflammatory marker and lipoprotein levels in patients with coronary heart disease - Sindu PC (International Journal of Medical Research and Review, 2016)
Background: C-Reactive Protein is a good marker of systemic inflammation which can be measured easily. Atherosclerosis lesions are intimal thickening of arteries. Inflammatory and immune cells constitute an important part of atheroma. C-RP levels at the upper end of the normal range indicate that a low level of inflammatory response has been initiated. Measurment of hs CRP provides a method to assess the risk of cardiovascular disease very early in life.Aim: Estimation of High sensitivity C-Reactive Protein (HS-CRP) levels which is a marker of inflammation in serum of normal people and patients with past history of myocardial infarction.Materials and Methods: Twenty six serum samples from patients with coronary heart disease (who had previous history of Myocardial Infarction) and twenty-one control samples and were included in the study. High sensitivity C-reactive protein and lipoprotein profile were estimated in patients with coronary heart disease and in age matched controls. Statistical Analysis- All data were represented as mean ± SD. Experimental data were statistically analyzed by students t’-test. For all analysis statistical significance was considered as p < 0.05.Results: Mean hs C-RP level is significantly elevated in patients who had myocardial infarction when compared with age matched controls. Total cholesterol, LDL cholesterol also found to be increased in individuals who had myocardial infarction.Conclusion: Inflammation plays an important role in myocardial infarction. Increased risk of MI is seen in those individuals who have higher levels of hsC-RP. There is also increase in total cholesterol and LDL cholesterol in subjects who had myocardial infarction when compared to controls. Coronary artery disease may be prevented by reducing the inflammation in addition to reducing the LDL cholesterol